Osservazioni sull’uso di yád in antico indiano (Atti del Sodalizio Glottologico Milanese, 2021)
This paper considers the placement of the complementizer yád within the sentence and the functional value of yád in Old Indian. It will be noted that thecomplementizer yád, like other subordinating conjunctions in some ancient and modern Indo-European languages, can be preceded by a topicalized or a focalized phrase in its clause. In particular, in R̥gVeda there are many cases where yád is preceded by an element which seems to have moved from inside the sentence and also cases where yád is preceded by the inflected verb. Morover, some cases will be discussed showing the use of yád to introduce clauses governed by verbs of saying and knowing, both in Vedic and in Sanskrit, and a possible syntactic analysis of these structures.
Keywords: Old Indian Syntax; Indo-European Syntax; Old Indian Subordination; Old Indian Left Periphery; Explicative Clauses